PERAN MASJID DALAM MEMPERSATUKAN UMAT ISLAM: STUDI KASUS MASJID AL-FATAH, PUCANGAN, KARTASURA - Syakirin Al-Ghazali (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2018)
Mosque is an instrument of empowerment of people who have a very strategic role in efforts to improve the quality and can unite the community. This article aims to describe the role of the Al-Fatah mosque as a pluralistic and socially pluralistic community empowerment center. The main data comes from interviews and observations, while the method used is qualitative descriptive. This article concludes that the empowerment of the pluralist society around Al-Fatah mosque is done by optimizing the role of all community groups in various mosque activities. The mosque can be the center of activity of all community groups because its activities are not limited to religious activities only, but cover other social social.